Agro-Industrial Wastes for Production of Biosurfactant by Bacillus subtilis ANR 88 and Its Application in Synthesis of Silver and Gold Nanoparticles - Rane, Ashwini N.; Baikar, Vishakha V.; Ravi Kumar, V.; Deopurkar, Rajendra L. (Frontiers in Microbiology, 2017)
Biosurfactants, surface-active amphiphilic compounds, despite having a wide range of applications, have a high cost of production, which severely restricts their use. For cheaper production of biosurfactant, we investigated the potential of the indigenously isolated biosurfactant producing organism, Bacillus subtilis ANR 88, to grow on different cheap carbon sources (molasses, whey, and extracts of potato peels, orange peels, banana peels and bagasse). We found that, B. subtilis ANR 88 used significant amounts of total sugar to produce cell biomass and biosurfactant. The biosurfactant production in minimal medium containing glucose as sole source of carbon was 0.207 g/l and the same with molasses as carbon source was 0.241 g/l. With whey as carbon source, isolate failed to produce biosurfactant. Amongst the extracts of the agro-wastes, the extracts of bagasse and orange peels gave 0.127 and 0.089 g/l of biosurfactant respectively. One-variable-at-a-time (OVAT) studies carried out to optimize the production of biosurfactant by B. subtilis ANR 88 resulted into maximum biosurfactant yield of 0.513 g/l in medium: molasses 4%, ammonium ferric citrate 0.25%, pH 7. Plackett–Burman design based statistical method for optimization increased the production of biosurfactant to 0.746 g/l, which is 3.6 fold of that produced on glucose. The biosurfactant produced by Bacillus subtilis ANR 88 was analyzed by Fourier Transform Infrared Spectroscopy (FT-IR); it showed that the biosurfactant contained alkyl as well as peptide groups. The biosurfactant of B. subtilis ANR 88 was found effective in the synthesis of silver as well as gold nanoparticles in the total absence of conventional chemical reducing agents. Interestingly, nanoparticles produced were almost uniform in their size and shapes i.e. spherical silver (4-18 nm) and hexagonal gold nanoparticles (40-60 nm), as evident in TEM images.